2006
DOI: 10.1002/jcp.20596
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl hydroxylase 3 (LH3) modifies proteins in the extracellular space, a novel mechanism for matrix remodeling

Abstract: Lysyl hydroxylase 3 (LH3), the multifunctional enzyme associated with collagen biosynthesis that possesses lysyl hydroxylase and collagen glycosyltransferase activities, has been characterized in the extracellular space in this study. Lysine modifications are known to occur in the endoplasmic reticulum (ER) prior to collagen triple-helix formation, but in this study we show that LH3 is also present and active in the extracellular space. Studies with in vitro cultured cells indicate that LH3, in addition to bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
82
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 60 publications
4
82
2
Order By: Relevance
“…Localization can be tissue-specific, may require proteolysis, and may be regulated by mechanisms such as alternative splicing or putative RNA editing (24,26,27). In this study, native skeletal muscle FKRP was detected as a smaller ϳ50-kDa protein in skeletal muscle (predicted core protein ϳ55 kDa).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Localization can be tissue-specific, may require proteolysis, and may be regulated by mechanisms such as alternative splicing or putative RNA editing (24,26,27). In this study, native skeletal muscle FKRP was detected as a smaller ϳ50-kDa protein in skeletal muscle (predicted core protein ϳ55 kDa).…”
Section: Discussionmentioning
confidence: 55%
“…FKRP as a molecular chaperone for DG processing and/or targeting, or vice versa, is an intriguing possibility. Whether FKRP activity is required at the sarcolemma for normal muscle function is unclear; however, known glycosyltransferases may possess enzymatic or lectin binding activity at the cell surface (23)(24)(25)30). Overall, our data indicate that FKRP is present at the muscle cell surface, associates with the DGC, and may have a unique role in the ␣DG processing pathway.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…2.4.1.66) activities in vitro (11)(12)(13). LH3 is functional in both the endoplasmic reticulum and extracellular space (14), and loss of LH3 leads to early embryonic lethality (15,16). We have reported recently that LH3 is also multifunctional in vivo and that especially the glucosyltransferase activity of LH3 is essential for normal embryonic development (16).…”
mentioning
confidence: 99%
“…9,15 This ancestral C. elegans LH is also able to glycosylate Hyl residues and, thus, is functionally similar to LH3. 9,13 Recently, Salo et al 16 found that LH3 is located in two compartments in tissues, in the endoplasmic reticulum and the extracellular space, and the partitioning varies with tissue type. Thus, LH3 may be functional both inside and outside of the cell.…”
Section: Introductionmentioning
confidence: 99%